Endoscopic resection of a huge orbital ethmoidal mucocele masquerading as dacryocystocele. (17th October 2018) - Wong, Eugene; Leith, Nicholas; Wilcsek, Geoff; Sacks, Raymond
Abstract : Paranasal mucoceles are cystic masses lined with epithelium thought to result from chronic obstruction of an impaired sinus ostia. If sufficiency large, they can cause ophthalmological sequelae including diplopia, visual acuity, globe displacement as well as the rhinological symptoms of facial pain and headache. We present the case of a 57-year-old man who presented with a 1-year history of epiphora and right globe prominence with associated diplopia. Imaging demonstrated a mass located within the medial aspect of the orbit, closely associated to the lamina papyracea and nasolacrimal duct consistent with a dacryocystocele. An alternate diagnosis of an ethmoidal mucocele was considered preoperatively following rhinologist opinion. Complete endoscopic resection of the cyst was undertaken. Histopathology confirmed diagnosis of an ethmoidal mucocele. Our report highlights mucocele should be considered in patients with chronic symptoms secondary to a mass situated in the nasolacrimal duct without radiological orbital bone destruction.